2013
DOI: 10.1364/ol.38.002174
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal beacon

Abstract: The controlled navigation of the axonal growth cone of a neuron toward the dendrite of its synaptic partner neuron is the fundamental process in forming neuronal circuitry. While a number of technologies have been pursued for axonal guidance over the past decades, they are either invasive or not controllable with high spatial and temporal resolution and are often limited by low guidance efficacy. Here, we report a neuronal beacon based on light for highly efficient and controlled guidance of cortical primary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…For our experiments, we utilized a 1,455-nm infrared laser ( Fig. 1a ), which created a continuous heat source that was substantially more powerful than those used in previous optical guidance experiments 2 3 4 5 6 7 8 9 10 ( Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our experiments, we utilized a 1,455-nm infrared laser ( Fig. 1a ), which created a continuous heat source that was substantially more powerful than those used in previous optical guidance experiments 2 3 4 5 6 7 8 9 10 ( Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…While chemical cues are the most intensively studied guidance factors 1 , physical guidance has recently been proposed. Of these, optical guidance is the representative non-invasive method for inducing attraction or retraction of growing neurites 2 3 4 5 6 7 8 9 10 . Various studies have utilized laser beams of different wavelengths to induce effective and accurate regulation of neurite outgrowth; however, the critical parameters and biological mechanism governing optical guidance remain elusive.…”
mentioning
confidence: 99%
“…Though light has been shown to act as an attractive cue while directly impinging on the growth cone (with specific irradiation schedules), we have utilized an at-a-distance effect using a weakly-focused NIR light source which we currently believe to be photothermal2829. For loop-formation reported here, axons advancing at a growth rate of > 20 μm/hr were randomly selected.…”
Section: Resultsmentioning
confidence: 99%
“…While existing optical methods are based on attractive-guidance principles, we have found that a near-infrared (NIR) laser beams can act as a repulsive cue2728. Here, we have utilized a weakly-focused NIR laser beam to guide rat cortical axons in a highly effective manner, which has allowed us to construct loops of varying radii and observe axonal fasciculation for the first time.…”
mentioning
confidence: 99%
“…As the axon senses the repulsive cue, it deviates from its initial path to avoid the light (Fig. 3.14 ) (Black et al 2013 ). It is believed that this is a photothermal phenomenon in which fi lopodia sense and respond to a laser induced thermal gradient.…”
Section: Neuronal Beaconmentioning
confidence: 99%